SOME PHYSICAL PROPERTIES OF HALF-HEUSLER COMPOUND NaYSi : FIRST-PRINCIPLES STUDY - Yasemin Çiftci (Journal of Amasya University the Institute of Sciences and Technology)
The structural, electronic, elastic and optic properties of NaYSi formed in the half-Heusler structure are studied by using ab-initio density-functional theory. The calculated equilibrium lattice constants are compaired with the available experimental and theoretical data. The elastic parameters have calculated. Computed elastic results prove that this compound were mechanically stable. The band gap of this compound predicted to be semiconductor. Further the phonon spectra and optical analysis have been obtained for the energy range of 0–40 eV.